2023
DOI: 10.1039/d3qi00420a
|View full text |Cite
|
Sign up to set email alerts
|

Lead-free hybrid indium perovskites with near-unity PLQY and white light emission using an Sb3+doping strategy

Abstract: Low-dimensional hybrid organic-inorganic metal halides (OIMHs) have been extensively investigated for their structural tunability and unique optoelectronic properties. However, the synthesis of highly photoluminescent lead-free OIMHs remains challenging. To address...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 62 publications
0
20
0
Order By: Relevance
“…Among lead-free 0D OIMHs, In-based materials have garnered attention and have made significant recent progress due to their stability, low-toxicity, and excellent luminescent properties. However, the luminescent efficiency of In-based metal halides remains poor. , Metal doping strategies have been verified as feasible methods to obtain enhanced PLQY. The highly efficient emission of In-based OIMHs through Sb doping has been reported in previous works. Yuan et al reported 0D In-based OIMHs, (C 7 H 8 N 3 ) 3 InBr 6 ·H 2 O and (C 11 H 24 N 2 ) 2 [InBr 6 ]­[InBr 4 ], with low emission efficiency. The PLQYs were significantly enhanced from <10 to 52 and 61% by Sb doping.…”
Section: Introductionmentioning
confidence: 78%
“…Among lead-free 0D OIMHs, In-based materials have garnered attention and have made significant recent progress due to their stability, low-toxicity, and excellent luminescent properties. However, the luminescent efficiency of In-based metal halides remains poor. , Metal doping strategies have been verified as feasible methods to obtain enhanced PLQY. The highly efficient emission of In-based OIMHs through Sb doping has been reported in previous works. Yuan et al reported 0D In-based OIMHs, (C 7 H 8 N 3 ) 3 InBr 6 ·H 2 O and (C 11 H 24 N 2 ) 2 [InBr 6 ]­[InBr 4 ], with low emission efficiency. The PLQYs were significantly enhanced from <10 to 52 and 61% by Sb doping.…”
Section: Introductionmentioning
confidence: 78%
“…The peak positions gradually shift toward lower angles with increasing Sb 3+ content, in accordance with the partial substitution of Hf 4+ by the larger Sb 3+ and indicating the successful incorporation of Sb 3+ into the (TMA) 2 HfCl 6 lattice. 38,39 Fig. 1c shows the Rietveld refinement of the XRD patterns of (TMA) 2 HfCl 6 :Sb 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…29,30 What's more, doping with appropriate amounts of Sb 3+ resulted in a spike in the PLQY of x%Sb 3+ :(DETA) 3 InCl 6 , and 0.005%Sb 3+ :(DETA) 3 InCl 6 can even emit white light when excited at a wavelength of 365 nm. 31 These findings not only suggest that the quantum structure, adjustable energy levels, and energy transfer between inorganic and organic components make low-dimensional OIHMHs exhibit excellent photophysical properties but also reveal that reasonable ion doping is an effective method to effectively improve the luminescence properties. 29 Herein, we report a series of zero-dimensional (0D) Inbased OIHMH, undoped and Sb 3+ -doped (Gua) 3 InCl 6 , which exhibit a broad yellow emission with a peak of 580 nm.…”
Section: Introductionmentioning
confidence: 90%
“…Although the above materials have excellent optical properties, researchers prefer to design a class of luminescent materials with excellent performance and nontoxic properties. Cs 2 InCl 5 ·H 2 O and (NH 4 ) 2 InCl 5 ·H 2 O cannot be excited by UV light, but 5%Sb 3+ :Cs 2 InCl 5 ·H 2 O and 5%Sb 3+ :(NH 4 ) 2 InCl 5 ·H 2 O both show a broadband yellow emission with a high PLQY of over 90%. , What’s more, doping with appropriate amounts of Sb 3+ resulted in a spike in the PLQY of x %Sb 3+ :(DETA) 3 InCl 6 , and 0.005%Sb 3+ :(DETA) 3 InCl 6 can even emit white light when excited at a wavelength of 365 nm . These findings not only suggest that the quantum structure, adjustable energy levels, and energy transfer between inorganic and organic components make low-dimensional OIHMHs exhibit excellent photophysical properties but also reveal that reasonable ion doping is an effective method to effectively improve the luminescence properties …”
Section: Introductionmentioning
confidence: 99%